Iterative methods for efficient sampling-based optimal motion planning of nonlinear systems - Ha, Jung-Su; Choi, Han-Lim; Jeon, Jeong Hwan (Zielona Góra: Uniwersytet Zielonogórski)
This paper extends the RRT* algorithm, a recently developed but widely used sampling based optimal motion planner, in order to effectively handle nonlinear kinodynamic constraints. Nonlinearity in kinodynamic differential constraints often leads to difficulties in choosing an appropriate distance metric and in computing optimized trajectory segments in tree construction.
Keywords: optimal motion planning; sampling-based algorithm; nonlinear dynamics